Asymmetric Synthesis of 1,2-Limonene Epoxides by Jacobsen Epoxidation - Zi-Yi Huang; Min-Ru Jiao; Xiu Gu; Zi-Ran Zhai; Jian-Qi Li; Qing-Wei Zhang (Georg Thieme Verlag KG, 2021)
Abstract This study reported an asymmetric synthesis of 1,2-limonene epoxides. The absolute stereochemistry was controlled by a Jacobsen epoxidation of cis-1,2-limonene epoxide (with diastereomeric excess of 98%) and trans-1,2-limonene epoxide (with diastereomeric excess of 94%), which could be used as important raw materials for the preparation of related cannabinoid drugs.